Green Tourist Behavior Model For Realizing Ecotourism Destinations Sustainable Artifcial-based Intelligence - Elfitra Desy Surya; Sri Rahayu; Rashdan Bin Rashid; Muhammad Faishal Annas (Yayasan Multidimensi Kreatif, 2025)
This study aims to test and analyze the influence of green perception on green tourism behavior. To test and analyze the influence of Green Environmental Concern on green tourism behavior. To test and analyze the influence of green tourism behavior on green tourism behavior. to test and analyze the influence of green perception on sustainable ecotourism. to test and analyze the influence of Green Environmental Concern on green tourism behavior. To test and analyze the influence of green perception on sustainable ecotourism mediated by green tourism behavior. To test and analyze the influence of Green Environmental Concern on sustainable ecotourism mediated by green tourism behavior. The population used in this study was 50,000 tourists with the slovin formula obtained a sample of 200 samples. The results of this study are that green perception has a positive and significant effect on green tourism behavior. Green Environmental Concern has a positive and significant effect on green tourism behavior. Green tourism behavior has a positive and significant effect on sustainable ecotourism. Green perception has a positive and significant effect on sustainable ecotourism. Green Environmental Concern for green tourism behavior. Green perception has a positive and significant effect on sustainable ecotourism mediated by green tourism behavior. Green Environmental Concern has a positive and significant effect on sustainable ecotourism mediated by green tourism behavior.